2019
DOI: 10.1186/s13046-019-1214-z
|View full text |Cite
|
Sign up to set email alerts
|

The roles of glucose metabolic reprogramming in chemo- and radio-resistance

Abstract: Reprogramming of cancer metabolism is a newly recognized hallmark of malignancy. The aberrant glucose metabolism is associated with dramatically increased bioenergetics, biosynthetic, and redox demands, which is vital to maintain rapid cell proliferation, tumor progression, and resistance to chemotherapy and radiation. When the glucose metabolism of cancer is rewiring, the characters of cancer will also occur corresponding changes to regulate the chemo- and radio-resistance of cancer. The procedure is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 189 publications
1
83
0
1
Order By: Relevance
“…miR-27a affects the response to chemotherapy Metabolic rewiring of cancer cells and cancer pathways activate mechanisms implicated in chemoresistance. 6,7 We, therefore, asked whether miR-27a was able to influence the CRC treatment response. Our in silico analysis of the TCGA-COAD dataset revealed that miR-27a expression was higher in the CRCs resistant to therapy (i.e.…”
Section: P-ampk/ampk Ratio Increased While the P-mtor/mtor Ratio Sligmentioning
confidence: 99%
“…miR-27a affects the response to chemotherapy Metabolic rewiring of cancer cells and cancer pathways activate mechanisms implicated in chemoresistance. 6,7 We, therefore, asked whether miR-27a was able to influence the CRC treatment response. Our in silico analysis of the TCGA-COAD dataset revealed that miR-27a expression was higher in the CRCs resistant to therapy (i.e.…”
Section: P-ampk/ampk Ratio Increased While the P-mtor/mtor Ratio Sligmentioning
confidence: 99%
“…Metabolic reprogramming is a distinctive hallmark of cancer. The reprogrammed glucose metabolism in tumorigenesis has been studied for many years (Kato et al, 2018;Lin et al, 2019). Additionally, the metabolism of amino acids, such as cysteine, homocysteine, glutamine, and methionine, are attracting increased attention in recent years (Gao et al, 2019;Lieu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the increase of glucose uptake and lactate secretion due to metabolic changes in malignant cells constitutes the Warburg effect, an essential step of carcinogenesis [2]. Alterations in glucose metabolism associated with dramatically increased proliferation activity, progression and development of chemo-/ radioresistance represent an important hallmark of malignancy [216]. Due to metabolic reprogramming, cancer cells exhibit increased levels of glucose uptake.…”
Section: Conclusion and Expert Recommendationsmentioning
confidence: 99%